Conservation and Utilisation of the Crocodilian Fauna of India - Murthy, T. S. N.; Menon, A. G. K. (Indian Forester, 1977)
The three species of crocodiles found in the Indian sub-region viz, the Mugger or Marsh Crocodile (Crocodilus palustris, the Estuarine Crocodile (Crocodilus porosus) and the Gharials (Gavialis gangeticus) are described together with a key of their identification. A short account of then feeding and breeding habits in given. An outline of the work now being done on crocodile farming in India is furnished.